Ã˜ÂªÃ˜Â·Ã™Ë†Ã™Å Ã˜Â± Ã™â€¦Ã˜Â§Ã˜Â¯Ã˜Â© Ã˜Â§Ã™â€žÃ™â€ Ã˜ÂÃ™Ë† Ã˜Â¹Ã™â€žÃ™â€° Ã˜Â£Ã˜Â³Ã˜Â§Ã˜Â³ Ã™â€¦Ã˜Â¯Ã˜Â®Ã™â€ž Ã˜Â§Ã™â€žÃ˜ÂªÃ™â€ Ã™Ë†Ã™Å Ã™â€¦ Ã˜Â§Ã™â€žÃ™â€¦Ã˜ÂºÃ™â€ Ã˜Â§Ã˜Â·Ã™Å Ã˜Â³Ã™Å Ã™â€˜ Ã˜Â§Ã™â€žÃ˜ÂªÃ˜Â¹Ã™â€žÃ™Å Ã™â€¦Ã™Å - Rowin, Inchinia Angger (Ali Muchasan, 2017)
Ã˜Â§Ã™â€žÃ™â€ Ã˜ÂÃ™Ë† Ã™Å Ã™Æ’Ã™Ë†Ã™â€ Ã™â€¦Ã™â€ Ã˜Â¸Ã™Ë†Ã™â€¦Ã˜Â© Ã˜Â§Ã™â€žÃ™â€šÃ™Ë†Ã˜Â§Ã˜Â¹Ã˜Â¯ Ã™Ë†Ã˜Â§Ã™â€žÃ™â€šÃ™Ë†Ã˜Â§Ã™â€ Ã™Å Ã™â€ Ã˜Â§Ã™â€žÃ˜Â¶Ã˜Â§Ã˜Â¨Ã˜Â·Ã˜Â© Ã™â€žÃ˜Â£Ã˜ÂÃ™Æ’Ã˜Â§Ã™â€¦ Ã˜Â§Ã™â€žÃ™â€žÃ˜ÂºÃ˜Â© Ã™Ë†Ã™â€¡Ã™Ë† Ã˜Â¹Ã™â€žÃ™â€¦ Ã™Å Ã˜Â¹Ã˜Â±Ã™Â Ã˜Â¨Ã™â€¡ Ã™Ë†Ã˜Â¸Ã™Å Ã™ÂÃ˜Â© Ã™Æ’Ã™â€ž Ã™Æ’Ã™â€žÃ™â€¦Ã˜Â© Ã˜Â¯Ã˜Â§Ã˜Â®Ã™â€ž Ã˜Â§Ã™â€žÃ˜Â¬Ã™â€¦Ã™â€žÃ˜Â© Ã™Ë†Ã˜Â¶Ã˜Â¨Ã˜Â· Ã˜Â£Ã™Ë†Ã˜Â§Ã˜Â®Ã˜Â± Ã˜Â§Ã™â€žÃ™Æ’Ã™â€žÃ™â€¦Ã˜Â§Ã˜Âª Ã™Ë†Ã™Æ’Ã™Å Ã™ÂÃ™Å Ã˜Â© Ã˜Â¥Ã˜Â¹Ã˜Â±Ã˜Â§Ã˜Â¨Ã™â€¡Ã˜Â§. Ã™â€žÃ˜ÂµÃ˜Â¹Ã™Ë†Ã˜Â¨Ã˜Â© Ã™â€šÃ™Ë†Ã˜Â§Ã˜Â¹Ã˜Â¯ Ã˜Â§Ã™â€žÃ™â€ Ã˜ÂÃ™Ë† Ã™Ë†Ã˜Â§Ã™â€žÃ˜ÂµÃ˜Â±Ã™Â Ã˜Â§Ã™â€žÃ˜ÂªÃ™Å Ã˜ÂªÃ™â€šÃ˜Â¯Ã™â€¦ Ã™â€žÃ™â€žÃ˜Â·Ã™â€žÃ˜Â¨Ã˜Â© Ã™ÂÃ™Å Ã˜ÂªÃ˜Â¹Ã™â€žÃ™â€¦Ã™â€¡Ã˜Â§ Ã™ÂÃ™Å Ã˜ÂÃ˜ÂªÃ˜Â§Ã˜Â¬ Ã˜Â§Ã™â€žÃ˜Â·Ã™â€žÃ˜Â¨Ã˜Â© Ã˜Â¥Ã™â€žÃ™â€° Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â§Ã˜Â¯Ã˜Â© Ã˜Â§Ã™â€žÃ˜ÂªÃ˜Â¹Ã™â€žÃ™Å Ã™â€¦Ã™Å Ã˜Â© Ã™Æ’Ã˜Â§Ã™â€žÃ™Ë†Ã˜Â³Ã™Å Ã™â€žÃ˜Â© Ã˜Â§Ã™â€žÃ˜ÂªÃ™Å Ã˜ÂªÃ˜ÂÃ™â€¦Ã™â€ž Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â¹Ã™â€žÃ™Ë†Ã™â€¦Ã˜Â§Ã˜Âª Ã™Ë†Ã˜Â§Ã™â€žÃ˜Â§Ã˜ÂªÃ˜Â¬Ã˜Â§Ã™â€¡Ã˜Â§Ã˜Âª Ã™â€žÃ™â€žÃ˜Â·Ã™â€žÃ˜Â¨Ã˜Â©Ã˜Å’ Ã™â€žÃ™Å Ã˜Â³ Ã™ÂÃ™â€šÃ˜Â· Ã™â€žÃ™â€žÃ˜Â·Ã™â€žÃ˜Â¨Ã˜Â© Ã˜Â¨Ã™â€ž Ã™â€žÃ™â€žÃ™â€¦Ã˜Â¹Ã™â€žÃ™â€¦Ã™Å Ã™â€ Ã™Ë†Ã˜ÂºÃ™Å Ã˜Â±Ã™â€¡Ã™â€¦ Ã˜Â£Ã™Å Ã˜Â¶Ã˜Â§. Ã™Ë†Ã™â€¦Ã™â€ Ã˜Â£Ã˜ÂÃ˜Â¯ Ã˜Â§Ã™â€žÃ™â€¦Ã˜ÂÃ˜Â§Ã™Ë†Ã™â€žÃ˜Â§Ã˜Âª Ã˜Â§Ã™â€žÃ˜ÂªÃ™Å Ã™â€šÃ˜Â§Ã™â€¦ Ã˜Â¨Ã™â€¡ Ã™â€¦Ã˜Â¹Ã™â€žÃ™â€¦ Ã™â€¦Ã˜Â§Ã˜Â¯Ã˜Â© Ã˜Â§Ã™â€žÃ™â€ Ã˜ÂÃ™Ë† Ã™â€žÃ˜ÂÃ™â€žÃ™â€˜ Ã˜ÂµÃ˜Â¹Ã™Ë†Ã˜Â¨Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â·Ã™â€žÃ˜Â¨Ã˜Â© Ã™ÂÃ™Å Ã™â€¦Ã˜Â§Ã˜Â¯Ã˜Â© Ã˜Â§Ã™â€žÃ™â€ Ã˜ÂÃ™Ë† Ã™Ë†Ã™â€¡Ã™Å Ã˜Â¨Ã˜ÂªÃ˜Â·Ã™Ë†Ã™Å Ã˜Â± Ã™â€¦Ã˜Â§Ã˜Â¯Ã˜Â© Ã˜Â§Ã™â€žÃ™â€ Ã˜ÂÃ™Ë† Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â¨Ã˜ÂªÃ™Æ’Ã˜Â± Ã™Ë†Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â´Ã™Ë†Ã™â€˜Ã™â€š Ã˜Â¹Ã™â€žÃ™â€° Ã˜Â´Ã™Æ’Ã™â€ž Ã˜Â§Ã™â€žÃ˜ÂªÃ™Æ’Ã™â€ Ã™Ë†Ã™â€žÃ™Ë†Ã˜Â¬Ã™Å Ã˜Â§ Ã˜Â¹Ã™â€žÃ™â€° Ã˜Â£Ã˜Â³Ã˜Â§Ã˜Â³ Ã™â€¦Ã˜Â¯Ã˜Â®Ã™â€ž Ã˜Â§Ã™â€žÃ˜ÂªÃ™â€ Ã™Ë†Ã™Å Ã™â€¦ Ã˜Â§Ã™â€žÃ™â€¦Ã˜ÂºÃ™â€ Ã˜Â§Ã˜Â·Ã™Å Ã˜Â³Ã™Å Ã™â€˜ Ã˜Â§Ã™â€žÃ˜ÂªÃ˜Â¹Ã™â€žÃ™Å Ã™â€¦Ã™Å